A multi-criteria approach of assessing groundwater potential, recharge and flow in the transboundary Tuli Karoo Basin. Issue 9 (11th August 2022) - Tinonetsana, Primrose C.; Gumindoga, Webster; Rwasoka, Donald T.
Abstract: Quantitative estimates of amount of groundwater resources are required in the transboundary Tuli Karoo Basin to better manage and promote sustainable conjunctive use of the aquifer. Unfortunately, such important data and information are lacking. The aim of this study was to map groundwater potential zones and model groundwater recharge as well as groundwater flow in the Tuli Karoo Basin (12, 164 km 2 ) using geospatial techniques. To delineate groundwater potential zones, nine thematic maps of groundwater conditioning factors were computed and weighted using Saaty's Analytical Hierarchy Process (AHP). To validate the groundwater potential map, a Kruskal–Wallis test was performed. Groundwater recharge and groundwater flow direction were estimated in a coupled Geographic Information System (GIS) and modelling environment using the soil–water–balance model (SWB) and British Geological Survey (BGS) groundwater tool, respectively. Results for groundwater potential mapping showed that the area is dominated by high ground water potential which covers about 57.8% (6, 915.1 km 2 ) of the basin. The Kruskal–Wallis test showed that the median values of the borehole yields vary significantly between the different groundwater potential zone classes ( P -value <0.0001). Estimated groundwater recharge using SWB model showed that the maximum annual potential recharge for the Tuli Karoo Basin was 13.2 mm/year for the 10-year period from 2010 to 2020. Results from the BGS tool for groundwater flow show that the dominant groundwater flow direction is southeast. The results showed that there is no link between groundwater flow direction and surface water flow direction. This study is relevant in water development policy, water-related development aid, community planning and technical decision making for hydrogeologists, catchment managers, water planners and non-specialists alike. HIGHLIGHTS: GIS and remote sensing can be used to map groundwater potential zones. Tuli Karoo basin has high groundwater potential. Study is relevant for water development policy, water-related development aid, community planning and technical decision making for hydrogeologists, catchment managers, water planners and non-specialists alike. More research is needed using field based data. Graphical Abstract